Kemampuan Keterampilan Membaca Arab antara Siswa Putra dan Putri di Madrasah Tsanawiyah - Sangidah, Siti; Sholihah, Rizki Amalia; Muqorrobin, Syamsul (Study Program of Arabic Language Teaching, 2022)
This study was written to determine the ability of Mahārah Qira'ah female students in grade IX of MTs Darul Muna Ponorogo, and to determine the factors causing the development of Mahārah Qira'ah in grade IX of MTs Darul Muna Ponorogo. This research uses a descriptive qualitative method by extracting data through observation (field observations), interviews, and documentation. The study results explain that the research was carried out at MTs Darul Muna Ponorogo, the objects in this study included male and female students in class IX of MTs Darul Muna Ponorogo and Arabic language teachers. The research was conducted by conducting written and oral tests with qualifications for reading fluency tests, the ability to understand the contents of the readings, and the ability to rewrite the contents of the readings that were read, to determine the students' Mahārah Qira'ah abilities. Interviews to determine the factors that influence the development of reading skills and madrasa documentation to find out the activities carried out to improve students' reading skills. The research concludes that Mahārah Qira'ah in female students is superior to male students. The development process of Mahārah Qira'ah is influenced by internal factors of students' motivation and interest in learning, the ability of each student's brain function. External factors include environmental factors of students from families, communities, schools, religious factors, cultural factors, and educational background of students.